“Despite you”: the cultural power of Chico Buarque in times of open defense of the brazilian workers party: O poder cultural de chico buarque em tempos de defesa aberta do partido dos trabalhadores - Ballerini, Franthiesco; Künsch, Dimas A. (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
During his career as an artist, Chico Buarque de Hollanda has worked, among others, in the areas of music and literature. His performance as an artist, that since 1989, openly supports the Brazilian Workers Party, is the object of study of this essay, in which it crosses the concepts of soft power (Joseph Nye) and symbolic power (Pierre Bourdieu). We come up with the concept of cultural power, understood as the power of artists that, with the product they generate, they seduce, influence, sell and, therefore, participate in human history in their own way. Using the Google Trends to detect the popularity of Chico Buarque, electing the essay as a way of thought expression and moving it in the scope of the so called South epistemologies (Boaventura de Sousa Santos), our main goal is to delimitate the possible meanings of the concept of cultural power, being guided by the following question: the political positioning of Chico Buarque, in times of crisis of the hard power of PT, affects his cultural power in Brazil and in the world?